The Mental Health of Adolescent Girls with Depressed Mothers: The Mediating Role of the Perception of Parental Styles. Issue 45 (8th August 2019) - Shahimi, Farnaz; Rahimi, Changiz; Mohamadi, Norolah
Abstract: Maternal depression, its effects on mothers' interactions with their children, and the different mechanisms of emotional and psychological disorders' transaction to children have been surveyed for the last few decades of research. The aim of this research was to find the mediating role of the perception of parental styles between the maternal depression symptoms and the mental health of their daughters. The participants included 284 mothers and their daughters from 8 different schools chosen randomly. Mothers completed the Beck Depression Inventory-II and examined using differential diagnosis interview based on DSM-V while adolescents completed the Parenting Style Questionnaire and Symptom Check List 90-R. The results showed the mediating role of the perception of authoritative and authoritarian styles of parenting ( p  ≥ 0.0001). Also, depression symptoms in mothers could predict the perception of parental styles. Additionally, the perception of authoritative and authoritarian parenting could predict the mental health of adolescents.